Perancangan Aplikasi Pengarsipan Surat Berbasis Web di PT. Kantor Pegadaian Wilayah I Medan - Aisyiyah, Siti R Nur; Suhardi, Suhardi (Journal of Information Systems and Technology Research, 2022)
Letter is a communication to convey written information by one party to another party. At the Medan Regional I Office, physically still using archive folders which are then stored in file cabinets, where this method is less efficient and takes a long time. In an agency or company, mail management is very important in the administrative process. So the researchers made an application design using the Dreamweaver editor and using the PHP programming language, with database processing using MySQL. So it is hoped that the mail management process is carried out properly, quickly and easily. With the E-Letter Archive application, it is hoped that it can reduce the use of a long time in filing letters, as well as reduce paper use, speed up the search for letters.